Load Frequency Control in Single-Area Power System Using Integral Control and Proportional Integral - Budi Wicaksono, Bagas; Wati, Trisna (Frontier Energy System and Power Engineering, 2020)
Load Frequency Control (LFC) had a vital role in the power system. To supply excellent quality electricity, LFC was required as the frequency stabilizer in the power plant because electrical energy should have a stable frequency (49–51 Hz in Indonesia). The unstable frequency in the power plant could potentially damage the household electronic devices that used the electricity from the power plant. The electrical energy frequency was influenced by generator speed rotation. When the load was high, the generator would have a slower rotation speed. The opposite also occurred; when the load was low, the generator rotation speed would increase. Thus, a surge in frequency would happen and could damage electronic devices. The LFC was the solution to this problem. This article used LFC equipped with Integral control and Proportional Integral simulated using MATLAB-SIMULINK and then conducted a comparison on both controllers.